Analisis Manajemen Sumber Daya Manusia dalam Meningkatkan Kinerja Tenaga Medis di Rumah Sakit - Purwadhi, Purwadhi; Widjaja, Yani Restiani; Irawati, Irfa; Lestari, Nike Dwi Putri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyze the role of human resource management (HRM) in improving the performance of medical personnel in hospitals. The method used is a descriptive study with a qualitative approach, involving interviews and observations of medical personnel and hospital management. The results of the study indicate that a strict recruitment and selection process, ongoing training programs, a transparent performance appraisal system, and fair compensation and incentives have a significant impact on improving the performance of medical personnel. Hospitals that implement effective HRM strategies can improve the quality of service, patient satisfaction, and loyalty of medical personnel. This study concludes that good HRM not only contributes to improving individual performance, but also supports the overall goals of the organization. The implications of this study indicate the importance of investing in HRM to create competent and motivated medical personnel, as well as to improve the quality of health services in hospitals.